Diversity in framework architecture of lanthanide-2,5-pyridinedicarboxylate-sulfate coordination polymers - M. Sinchow (2019)
© 2019 Elsevier Inc. New series of [Ln2 (pydc)2(SO4) (H2O)x]·yH2O (H2pydc = 2,5-pyridinedicarboxylic acid), differing in number of the coordinating (x) and the crystallizing (y) water, have been hydrothermally synthesized and characterized: (i) x = 2, y = 6, and Ln = La, Pr and Nd; (ii) x = 3, y = 2 and Ln = Pr and Nd; and (iii) x = y = 0 and Ln = Pr and Nd. Influences of the subtle change in reaction temperature (80–180 °C) and time (1–7 days) on x and y values, and structural diversity of the titled complexes are reported. The association between x and y values and the hydrogen bonding interactions facilitated by the water molecules, the aromatic π-π interactions of the pydc2− ligand, as well as the coordination modes of both pydc2− and sulfate is discussed. Dissimilar thermogravimetric behaviors and the framework stabilities are presented.